Accelerated hydrothermal aging of biocarbon reinforced nylon biocomposites. (May 2017) - Ogunsona, Emmanuel O.; Misra, Manjusri; Mohanty, Amar K.
Abstract: Nylon/biocarbon biocomposites show great potential for semi-structural auto-part applications due to their enhanced mechanical and physical properties. However, the long term durability of these biocomposites has never been studied before. The durability of the biocomposite was compared to that of talc reinforced nylon composite at 20 wt. % for both composites. They were subjected to accelerated and aggressive conditioning by complete immersion in water at 85 °C for prolonged periods of time up to 28 days. The water uptake of the nylon/biocarbon biocomposite was reduced in comparison to that of the nylon suggesting that biocarbon particles act as a barrier while also concentrating the absorbed moisture within its pores and around the interface with nylon. Thermal properties revealed little changes in the crystallinity of the nylon/biocarbon composites. However, the glass transition temperature was observed to decrease significantly after conditioning due to the presence of bound water molecules within the amorphous phase of nylon. The impact strength remained mostly unchanged even after conditioning, suggesting interaction between biocarbon and nylon to restrict the chain mobility and thereby annulling the effect of moisture on the nylon. The morphology of the impact fractured surface of the conditioned sample revealed two distinct phases. One was significantly affected by moisture, revealed swelling and debonding of biocarbon particles from the nylon matrix while the other remained unchanged when compared to that of the unconditioned sample.